Dog days of history : the incredible story of our best friends - Albee, Sarah (National Geographic, 2018)
Explores the history of the relationship between dogs and humans, stretching back to the domestication of the wolf 15,000 years ago to modern canine pets and culture, such as Lassie and the famous dogs of the Queen of Britain. Includes a bibliography and references to sources.